Effects of Measurement Configurations on the Sensitivity of Morpho Butterfly Scales Based Chemical Biosensor - Dong, Zhengqiong; Zhao, Hang; Nie, Lei; Tang, Shaokang; Li, Chenyang; Wang, Xuanze (Frontiers in Physics, 2022)
The Morpho butterfly wing with tree-shaped alternating multilayer is an effective chemical biosensor to distinguish between ambient medium, and its detection sensitivity is inextricably linked to the measurement configuration including incident angle, azimuthal angle, and so on. Because the effects and the selection of measurement configuration have rarely discussed in the previous study. In this work, the model of the Morpho butterfly wing is built using the rigorous coupled-wave analysis (RCWA) method by considering its profile is a rectangular-groove grating. On basis of the above medal, the reflectivity of different diffraction orders at a different incident angle and azimuthal angle is calculated, and the influence of incident angle and azimuthal angle on performance of Morpho butterfly scales-based biosensor is analyzed. The optimal incident angle at each azimuthal angle is given according to the proposed choice rule, then the azimuthal angle and the corresponding incident angle can be selected further.